Evaluation of Lung Function and Clinical Features of the Ultrasound-Guided Stellate Ganglion Block With 2 Different Concentrations of a Local Anesthetic: A Randomized Controlled Trial. (April 2017) - Kim, Won-Joong; Park, Hahck Soo; Yi, Myung Sub; Koo, Gill-Hoi; Shin, Hwa-Yong
Abstract : BACKGROUND: One possible complication of stellate ganglion block (SGB) is respiratory compromise. No study has yet addressed the comparison of its effect on lung function and clinical features, including Horner's syndrome, changes in temperature, sensory and motor functions, and adverse events of lower versus higher concentrations (LC and HC, respectively) of local anesthetics in an ultrasound-guided SGB. METHODS: Fifty patients were randomized into 1 of 2 groups: the LC group (5 mL of 0.5% mepivacaine) and the HC group (5 mL of 1% mepivacaine). One anesthesiologist performed a C6- SGB under ultrasound guidance. Our primary objective was to compare LC and HC of a local anesthetic in terms of its effect on lung function, and the secondary objective was to compare the clinical features between LC and HC of a local anesthetic. Lung function was compared between the 2 groups using the Mann-Whitney U test. RESULTS: The forced vital capacity at 20 minutes post-SGB was not significantly different between the HC and the LC groups ( P = .360); the median difference (95% confidence intervals [CI]) was 1 (−1 to 8). Other parameters of lung function were comparable with the forced vital capacity. Patients in the HC group had significantly greater sensory changes than those in the LC group (% decrease compared with the unblocked side); 95.4 ± 2.1 (CI: 91.11–99.73) vs 87.3 ± 3.5 (CI: 80.12–94.49). CONCLUSIONS: Lung function between the LC and HC groups after SGB did not differ significantly. Clinical features between the 2 groups also did not differ clinically, except that patients in the HC group had significantly greater sensory loss in the C6 dermatomes.